Curcuma and Scutellaria plant extracts protect chickens against inflammation and Salmonella Enteritidis infection - Varmuzova, Karolina; Matulova, Marta Elsheimer; Gerzova, Lenka; Cejkova, Darina; Gardan-Salmon, Delphine; Panhéleux, Marina; Robert, Fabrice; Sisak, Frantisek; Havlickova, Hana; Rychlik, Ivan (Poultry science, 2015)
After a ban on the use of antibiotics as growth promoters in farm animals in the European Union in 2006, an interest in alternative products with antibacterial or anti-inflammatory properties has increased. In this study, we therefore tested the effects of extracts from Curcuma longa and Scutellaria baicalensis used as feed additives against cecal inflammation induced by heat stress or Salmonella Enteritidis (S. Enteritidis) infection in chickens. Curcuma extract alone was not enough to decrease gut inflammation induced by heat stress. However, a mixture of Curcuma and Scutellaria extracts used as feed additives decreased gut inflammation induced by heat or S. Enteritidis, decreased S. Enteritidis counts in the cecum but was of no negative effect on BW or humoral immune response. Using next-generation sequencing of 16S rRNA we found out that supplementation of feed with the 2 plant extracts had no effect on microbiota diversity. However, if the plant extract supplementation was provided to the chickens infected with S. Enteritidis, Faecalibacterium, and Lactobacillus, both bacterial genera with known positive effects on gut health were positively selected. The supplementation of chicken feed with extracts from Curcuma and Scutelleria thus may be used in poultry production to effectively decrease gut inflammation and increase chicken performance.
Keywords: kur domácí; Poultry Diseases; Inflammation; rostlinné extrakty; Animal Feed; Chickens; RNA, Ribosomal, 16S; mikrobiota; antibakteriální látky; Salmonella; Curcuma; flavonoid; šišák; Microbiota; krmivo pro zvířata; salmonelová infekce u zvířat; potravní doplňky; dieta; Dietary Supplements; zánět; nemoci drůbeže; Salmonella Infections, Animal; Animals; Plant Extracts; Anti-Bacterial Agents; zvířata; feed; inflammation; Diet; RNA ribozomální 16S; antiflogistika; Salmonella enteritidis; Anti-Inflammatory Agents; Scutellaria; chicken